Aesthetics of life in landscape poetry by Nam Chou Poets (1973-1990) - Foo, Ai Peng (2015)
The classical landscape poetry has its own function of aesthetics of life according to the traditional Chinese literary criticism. This thesis explores the structure of aesthetics of life of the contemporary classical landscape poetry created by the NamChou PoetryAnthologyin Malaysia from 1973 to 1990. To expose the nature of the structure, this thesis also indicates it from the perspective of aesthetics of life of Tang’s landscape poetry. Throughout the study, the implication of the NamChou Poetry’s landscape poetry can be divided thematically into three phases: the Autumn Period (1973), the Mount and Water Period (1974-1980), and the Mount Period (1981-1990). However, the nature of the whole landscape poetries can be aesthetically summarized as quite similar to the leisure poetry of the great landscape poet in the Tang, Bai Juyi (772-846), which is smooth and graceful in feeling and its beauty, plain and fascinating. In a nutshell, for the NamChou Poetry’spoets, landscape poetry characterizes different level of affection expressed, just to fulfil the life aesthetics with self-contentment and spiritual calmness.